HUBUNGAN KECERDASAN EMOSIONAL DAN TINGKAT STRES DENGAN KESEHATAN MENTAL MAHASISWA TINGKAT PERTAMA PRODI KEPERAWATAN UNIVERSITAS AL-IRSYAD CILACAP - Engkartini Engkartini (IKesT Muhammadiyah Palembang, 2024)
Mental health is a state of well-being of individuals who realize their personal potential, are able to overcome current problems and deal with the stress of life normally and can work effectively. Aims to determine the relationship between emotional intelligence and stress levels and mental health. The design of this research is quantitative research with a cross sectional approach. The total sample was 91 students and used a total sampling technique. The research instruments consisted of an emotional intelligence questionnaire, the PSS-10 questionnaire to measure stress levels, and the SRQ questionnaire to measure mental health. The data that has been obtained is then carried out a Spearman rank statistical test. The research results show that there is a relationship between emotional intelligence and mental health with very low strength (p value = 0.049). Meanwhile, there is no relationship between stress levels and mental health with low relationship strength (p value = 0.235). So, it can be concluded that there is a significant relationship between emotional intelligence and mental health. Keywords: Mental health, Emotional intelligence, Stress levels